The Factors Influencing Import of Raw Crystal Sugar From Thailand to Indonesia - Cayani, Lia Regita; Sitepu, Indrawaty; Nababan , Manaor Bismar Posman (Action Research Literate, 2024)
This research aims to determine what factors influence the import of raw crystal sugar from Thailand to Indonesia. The method for determining regions is purposively used, namely, in Indonesia. The data collection method used in this research is secondary data. The data analysis method used is a multiple linear regression test with the Ordinary Least Square or OLS method. The results of this research are as follows: (1) The regression model used passed the classical assumption test, namely Multicollinearity, Heteroscedasticity, Autocorrelation, and Normality. (2). Factors that have a significant positive effect on the quantity of imported raw crystal sugar (raw sugar) from Thailand to Indonesia are GDP (gross domestic product) per capita. In contrast, one factor that significantly affects the number of imports of raw crystal sugar (raw sugar) from Thailand to Indonesia is the price of imported sugar. (3). Factors that do not significantly influence the quantity of raw crystal sugar imports from Thailand to Indonesia are sugar import tariffs and consumption rates